2021
DOI: 10.1038/s41598-021-91951-4
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodically driven transcriptome-wide changes in the hypothalamus reveal transcriptional differences between physiologically contrasting seasonal life-history states in migratory songbirds

Abstract: We investigated time course of photoperiodically driven transcriptional responses in physiologically contrasting seasonal life-history states in migratory blackheaded buntings. Birds exhibiting unstimulated winter phenotype (photosensitive state; responsive to photostimulation) under 6-h short days, and regressed summer phenotype (photorefractory state; unresponsiveness to photostimulation) under 16-h long days, were released into an extended light period up to 22 h of the day. Increased tshβ and dio2, and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(100 reference statements)
1
4
0
Order By: Relevance
“…A study on redheaded buntings reported a significant increase after exposure to a single long day in mRNA levels of Pax6 (paired box 6) involved in the activation of Eya3 (Eye absent 3, important for photoperiodic induction), Tshβ , Dio2 and Rhodopsin genes [ 64 ]. A similar significant increase in the mRNA expression of Tshβ and Dio2 and a decrease in Dio3 level was found by hour 18 of the first long day in migratory blackheaded bunting ( Figure 2 , [ 65 ]). Interestingly, the peak mRNA expression of Tshβ and Dio2 occurred during hour 14–16 of the day, consistent with the circadian rhythm in photo-inducibility of the photoperiodic response system in buntings [ 66 ].…”
Section: Unraveling the Genetic Control Of Migratory Behaviorsupporting
confidence: 66%
“…A study on redheaded buntings reported a significant increase after exposure to a single long day in mRNA levels of Pax6 (paired box 6) involved in the activation of Eya3 (Eye absent 3, important for photoperiodic induction), Tshβ , Dio2 and Rhodopsin genes [ 64 ]. A similar significant increase in the mRNA expression of Tshβ and Dio2 and a decrease in Dio3 level was found by hour 18 of the first long day in migratory blackheaded bunting ( Figure 2 , [ 65 ]). Interestingly, the peak mRNA expression of Tshβ and Dio2 occurred during hour 14–16 of the day, consistent with the circadian rhythm in photo-inducibility of the photoperiodic response system in buntings [ 66 ].…”
Section: Unraveling the Genetic Control Of Migratory Behaviorsupporting
confidence: 66%
“…At the expression level, Photoperiodism impacted gene expression levels in the hypothalamus [ 4 , 5 , 48 ]. Gene expression in the hypothalamus was associated with increased TSHβ and dio2 mRNA levels and decreased dio3 mRNA levels under long light conditions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the expression level, Photoperiodism impacted gene expression levels in the hypothalamus [ 4 , 5 , 48 ]. Gene expression in the hypothalamus was associated with increased TSHβ and dio2 mRNA levels and decreased dio3 mRNA levels under long light conditions [ 48 ]. As expected, the expression level of dio2 observed a significant increase in RD after long light exposure in the hypothalamus of Magang geese.…”
Section: Discussionmentioning
confidence: 99%
“…A long-day photoperiod caused a profound change in the architecture and function of the testes of Magang geese. Although transcriptome responses to photoperiod effects on the testis have been extensively studied in avians ( Sun et al, 2020 ; Sharma, et al, 2021 ), relatively little is known about the epigenetic impact of testicular regression during long-day photoperiods. Current knowledge is primarily based on genetic analyses of candidate genes associated with endocrine regulation of the HPG axis ( Leska, et al, 2012 ; Gumułka, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%